Effectiveness of Interactive Educational Applications in Improving the Content Mastery of Selected Grade 9 AP Students - Frias, Jo Ann Bernafe; Flores, J.A.; F, M.T. (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Preserving students' engagement and drive in a digital setting poses a formidable obstacle for instructors, particularly amidst the pandemic. Due to the COVID-19 pandemic, teachers have been required to modify their instructional approaches and devise novel tactics to promote academic involvement. This study conducted action research to assess the efficacy of Interactive Educational Applications, such as Kahoot!, Quizizz, and Jamboard, in enhancing topic comprehension in Araling Panlipunan (AP) 9. It additionally investigated student contentment and the challenges faced during the integration of these technologies. The study utilized a mixed-method approach, incorporating both quantitative and qualitative methods. The sample consisted of 30 9th-grade students selected through convenience sampling. The results indicated a substantial statistical difference between the pre-test and post-test scores in AP 9 when Interactive Educational Applications were utilized. With 29 degrees of freedom and a significance level of 0.05, the computed t-value of +17.013 was higher than the critical value of +2.0457. Furthermore, the p-value of 0.0000 was below the significance level of 0.05, suggesting a substantial disparity between the two paired samples. The 95% confidence interval, which extends from -8.588 to -6.745, excludes zero. This provides more evidence that the utilization of Interactive Educational Applications greatly improved students' comprehension of Araling Panlipunan 9. An Interactive Educational Applications satisfaction assessment was undertaken through a Focus Group Discussion (FGD) to gauge student satisfaction. The majority of participants indicated that these applications had a good influence on their ability to master the topic in AP. Nevertheless, children encountered various obstacles throughout the intervention, including inadequate internet connectivity, distractions within their households, and subpar cell phones.